Application of Spa-Gene as A Marker of Molecular Epidemiology in the Case of Methicillin-Resistant Staphylococcus Aureus (MRSA) Which its from Dairy Cows in Surabaya Region - Asri Rizky; Mustofa Helmi Effendi; Jola Rahmahani (Jurnal Kedokteran Hewan, 2021)
The aim of this study was to isolate and identify the strain of methicillin-resistant Staphylococcus aureus (MRSA) from cow’s milk in Surabaya and to determine the fragment Spa-Gene in MRSA strains. There were 50 samples of cow’s milk obtained from four dairy farms. From 50 tested samples, 19 samples (38%) were positive for Staphylococcus aureus. Antibiotic sensitivity test using oxacillin and erythromycin showed that 6 samples were resistant to the antibiotic oxacillin and 6 samples were resistant to erythromycin. MRSA confirmation tests that were conducted on 6 samples revealed 5 positive results for the MRSA strain. Electrophoresis of Polymerase Chain Reaction (PCR) product showed that 4 out of 5 samples were positive for the presence of the Spa-Gene fragment. The research results showed that there were 3 models of Spa-Gene fragments; the first had a length of 90 bp and 140 bp, the second had a length of 140 bp, and third had a length of 90 bp. This study revealed the nature of Spa-Gene polymorphism of MRSA strains isolated from milk samples. It was concluded that the Spa-Gene can be used as a molecular epidemiological marker of the MRSA strain.